Co-construction of a national curriculum: the role of teachers as curriculum policy makers in Wales - Tom Crick (European Conference on Educational Research (ECER 2019), 2019)
Emergent worldwide curriculum policy since the turn of the millennium has placed a strong emphasis on the central role of teachers as curriculum makers (Priestley & Biesta, 2013). Supra-level curriculum discourses (Thijs & van den Akker, 2009), propagated by organisations such as the OECD have extolled the benefits of school autonomy and the agency of teachers as local curriculum makers with expertise in their own localities. National/state macro-level curriculum policies have explicitly positioned teachers as agents of change and active curriculum makers with local flexibility to decide curricular content and pedagogic approaches (e.g. the New Zealand Curriculum, the Singapore Curriculum, Hong Kong’s Curriculum Framework, Scotland’s Curriculum for Excellence, Ireland’s Junior Cycle Curriculum). Teacher involvement in curriculum making has tended to be restricted to curriculum making activity at the meso-level (for example, activity by district and regional agencies to support curriculum making in schools) and micro-level (school-based curriculum development) of education systems. Systematic and large-scale involvement by teachers as [relatively] autonomous leaders of macro-level curriculum making (i.e. the formation of national policy) has been less common. While the engagement of teachers in the development of the new curricula has been commonplace, this has tended to comprise consultation (e.g. in Ireland’s Junior Cycle reforms) or minimal autonomy in curriculum writing (e.g. the secondment of teachers under the direction of national education officials to work on writing the learning outcomes in Scotland’s Curriculum for Excellence).This symposium focuses on three jurisdictions -- British Columbia (Canada), Wales and the Netherlands -- where teachers have been taken a more active role -- in principle at least -- as autonomous curriculum makers. The three cases explore the nature and extent of teachers’ roles in the development of national/state curriculum policy. They illustrate how teachers’ inputs shape the emergent policy, and examine how such engagement develops their agency as curriculum makers.